A comparison of TRECs and flow cytometry for naive T cell quantification. (27th October 2017) - Adams, S. P.; Kricke, S.; Ralph, E.; Gilmour, N.; Gilmour, K. C.
Summary: Assessment of thymic output by measurement of naive T cells is carried out routinely in clinical diagnostic laboratories, predominantly using flow cytometry with a suitable panel of antibodies. Naive T cell measurements can also be made using molecular analyses to quantify T cell receptor excision circle (TRECs) levels in sorted cells from peripheral blood. In this study we have compared TRECs levels retrospectively with CD45RA + CD27 + T cells and also with CD45RA + CD31 + T cells in 134 patient samples at diagnosis or during follow‐up. Both panels provide naive T cell measurements that have a strongly positive correlation with TRECs numbers and are suitable for use with enumerating naive T cell levels in a clinical laboratory. Abstract : Naïve T cell measurement is essential in assisting diagnosis of primary immunodeficiency. This can be carried out using a combination of both flow cytometry and TRECs measurement. We show a strong positive correlation between TRECs levels and either CD45RA+CD27+ T cells or CD45+CD31+ T cells but not with CD3+ T cells.